Reading changes in children and adolescents with dyslexia after transcranial direct current stimulation. Issue 5 (23rd March 2016) - Costanzo, Floriana; Varuzza, Cristiana; Rossi, Serena; Sdoia, Stefano; Varvara, Pamela; Oliveri, Massimiliano; Koch, Giacomo; Vicari, Stefano; Menghini, Deny
Abstract : Noninvasive brain stimulation offers the possibility to induce changes in cortical excitability and it is an interesting option as a remediation tool for the treatment of developmental disorders. This study aimed to investigate the effect of transcranial direct current stimulation (tDCS) on reading and reading-related skills of children and adolescents with dyslexia. Nineteen children and adolescents with dyslexia performed different reading and reading-related tasks (word, nonword, and text reading; lexical decision; phonemic blending; verbal working memory; rapid automatized naming) in a baseline condition without tDCS and after 20 min of exposure to three different tDCS conditions: left anodal/right cathodal tDCS to enhance left lateralization of the parietotemporal region, right anodal/left cathodal tDCS to enhance right lateralization of the parietotemporal region, and sham tDCS. In text reading, results showed a significant reduction in errors after left anodal/right cathodal tDCS and an increase in errors after left cathodal/right anodal tDCS. No effect was found in the other reading and reading-related tasks. Our findings indicate for the first time that one session of tDCS modulates some aspects of reading performance of children and adolescents with dyslexia and that the effect is polarity dependent. These single-session results support a potential role of tDCS for developing treatment protocols and suggest possible parameters for tDCS treatment customization in children and adolescents with dyslexia.